POTENTIAL FOR PATIENTS AND PATIENT-DRIVEN ORGANIZATIONS TO IMPROVE EVIDENCE FOR HEALTH TECHNOLOGY ASSESSMENT. (20th November 2015) - Low, Eric
Abstract : This article gives a patient organization's perspective on health technology assessments (HTAs) and the role that such organizations can, and should, play in them.